2016
DOI: 10.18632/oncotarget.8967
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of endostar combined with taxane-based regimens for HER-2-negative metastatic breast cancer patients

Abstract: The purpose of the present study was to prospectively evaluate the efficacy and safety of endostar, a recombinant product of endostatin, combined with taxane-based regimens for HER-2 negative metastatic breast cancer (MBC) patients. Women with ages between 18–70 years with histologically confirmed MBC documented as HER-2-negative were included. Endostar was administered at 7.5 mg/m2, d1–14, q21d and was continued until progressive disease, unacceptable toxicity, consent withdrawal, or completion of 24 months o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…We evaluated the toxicity of rES-CSP according to the changes of the body weight and the visceral organ histomorphology, and confirmed that rES-CSP has no significant side effects, can be as a safe candidate drug for anti-HCC. The results in this study were consistent with previous reports 16 , 33 .…”
Section: Discussionsupporting
confidence: 94%
“…We evaluated the toxicity of rES-CSP according to the changes of the body weight and the visceral organ histomorphology, and confirmed that rES-CSP has no significant side effects, can be as a safe candidate drug for anti-HCC. The results in this study were consistent with previous reports 16 , 33 .…”
Section: Discussionsupporting
confidence: 94%
“…Rh-endostatin combined with GP chemotherapeutic regimen in the treatment of metastatic triple-negative breast cancer was also shown to have synergistic effects, demonstrated by the prolonged median TTP without an increase in the adverse events [43]. Hu et al [44] evaluated the efficacy and safety of rh-endostatin combined with taxanebased regimens in patients with HER-2-negative metastatic breast cancer. Among the total of 57 patients, the ORRs of all the patients, or patients who previous received first-line, second-line or third-line chemotherapies, were 68.4%, 79.3%, 54.5%, and 16.7%, respectively.…”
Section: Breast Cancermentioning
confidence: 99%
“…Hu et al [ 44 ] evaluated the efficacy and safety of rh-endostatin combined with taxane-based regimens in patients with HER-2-negative metastatic breast cancer. Among the total of 57 patients, the ORRs of all the patients, or patients who previous received first-line, second-line or third-line chemotherapies, were 68.4%, 79.3%, 54.5%, and 16.7%, respectively.…”
Section: Clinical Utility Of Rh-endostatin In Cancer Treatmentmentioning
confidence: 99%
“…For example, a study of the combination of Endostar with taxane-based regimens in breast cancer showed that the vast majority of patients experienced neutropenia (80.7%) and leukopenia (77.2%) [28].…”
Section: Discussionmentioning
confidence: 99%